The relationship between human capital and the performance of the entrepreneur in the retail industry in Kinshasa - Kongo, Michael (My University, 2014)
Could not copy Abstract
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.
Keywords: Entrepreneurship; Human capital; Retail industry; Education; Performance